2004
DOI: 10.1158/1078-0432.ccr-0833-3
|View full text |Cite
|
Sign up to set email alerts
|

Deguelin-Induced Inhibition of Cyclooxygenase-2 Expression in Human Bronchial Epithelial Cells

Abstract: The increased expression of cyclooxygenase (COX)-2 significantly enhances carcinogenesis and inflammatory reactions, and its regulation may be a reasonable target for cancer chemoprevention. We demonstrated previously that deguelin inhibits proliferation of premalignant human bronchial epithelial (HBE) cells, such as 1799 cells and squamous HBE cells, by regulating phosphatidylinositol-3-kinase Akt activity, which is involved in COX-2 expression. We sought to determine the effect of deguelin on COX-2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 23 publications
4
44
1
Order By: Relevance
“…Furthermore, our results that deguelin down-regulates cyclin D1 expression are in agreement with previous reports (13) that showed that downregulation of cyclin D1 is responsible for cell cycle arrest at the G 0 /G 1 phase. Similarly, our findings that deguelin suppresses NF-B-regulated COX-2 expression are in agreement with a previous report involving human bronchial epithelial cells (12).…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, our results that deguelin down-regulates cyclin D1 expression are in agreement with previous reports (13) that showed that downregulation of cyclin D1 is responsible for cell cycle arrest at the G 0 /G 1 phase. Similarly, our findings that deguelin suppresses NF-B-regulated COX-2 expression are in agreement with a previous report involving human bronchial epithelial cells (12).…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, deguelin treatment even at 1 mM showed significant decrease in lung epithelial cell lines. Similarly, cytotoxic effects of L80 on vascular endothelial and retinal epithelial cells were less compared with deguelin ( Fig Blockade of the C-terminal Hsp90 ATP Binding Domain by L80 effects on normal HBE cells at in vitro concentrations that are attainable in vivo (Lee et al, 2004). Hence, we first examined the effects of L80 on viability of NSCLC cell lines (i.e., H1299, A549, H460, and H226B).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, deguelin selectively blocks Akt activity in a phosphoinositide 3-kinase (PI3K)-dependent or -independent manner, thereby, diminishing the activity of a major anti-apoptotic pathway (9,10). Additionally, deguelin strongly inhibits cyclooxygenase (COX)-2 expression in squamous HBE cells, without affecting COX-1 protein level (11).…”
Section: Introductionmentioning
confidence: 99%